2022
DOI: 10.1080/21655979.2022.2071023
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human klotho protects against hydrogen peroxide-mediated injury in human retinal pigment epithelial cells via the PI3K/Akt-Nrf2/HO-1 signaling pathway

Abstract: Globally, age-related macular degeneration (AMD) is a common irreversible ophthalmopathy. Oxidative stress of retinal pigment epithelial cells is involved in AMD occurrence and development. Klotho is an anti-aging protein with antioxidant properties. We investigated the protective properties of Klotho on hydrogen peroxide (H 2 O 2 )-induced injury of retinal pigment epithelial cells (ARPE-19 cells) and its associated pathomechanisms. We found that Klotho pretreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
(46 reference statements)
2
5
0
Order By: Relevance
“…This suggests that the protective role of Klotho against oxidative stress may be attributed to the decrease in AKT-mTOR signaling, leading to an increase in FOXO3a activity and catalase levels. Our data reinforces the hypothesis that Klotho is an anti-aging protein with antioxidant properties 45 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that the protective role of Klotho against oxidative stress may be attributed to the decrease in AKT-mTOR signaling, leading to an increase in FOXO3a activity and catalase levels. Our data reinforces the hypothesis that Klotho is an anti-aging protein with antioxidant properties 45 .…”
Section: Discussionsupporting
confidence: 91%
“…Previous literature has reported that Klotho pretreatment for 24 hours can protect retinal pigment epithelial cells from H 2 O 2 -induced cell death by decreasing cleaved-caspase 3 and Bax levels and increasing antioxidant activity such as superoxide dismutase (SOD2) and catalase (CAT) 45 . This suggests that the protective role of Klotho against oxidative stress may be attributed to the decrease in AKT-mTOR signaling, leading to an increase in FOXO3a activity and catalase levels.…”
Section: Discussionmentioning
confidence: 99%
“…The disease can be effectively slowed down by interfering with the functions of human retinal pigment cells. For example, sulforaphane ameliorates amyloid-β-induced injury in RPE cells ( 15 ), recombinant human klotho protects against hydrogen peroxide-mediated injury in human retinal pigment epithelial cells ( 16 ), and baicalin suppresses AMD in vitro and in vivo ( 17 ). In AMD, functional changes in the RPE play an important role; neovascularization is particularly important, and its occurrence is closely related to the proliferation and activity of vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Prior literature indicates that a 24-h pretreatment with Klotho can protect retinal pigment epithelial cells from H 2 O 2 -induced cell death. This protection is achieved by reducing cleaved-caspase 3 and Bax levels, and enhancing antioxidant activity, such as SOD2 and CAT 54 . These findings suggest that Klotho’s protective role against oxidative stress could be attributed to a decrease in AKT-mTOR signaling, which subsequently leads to an increase in FOXO3a activity and catalase levels.…”
Section: Discussionmentioning
confidence: 99%